Evaluation of the effectiveness of the concrete protection channel for the urban expansion area of the western part from the risk of flooding, the case of the city of M’sila - Algeria - Gagui, Fateh; Redjem, Ali; Ghachi, Azzdine; Mezali, Farouk (Technium Social Sciences Journal, 2023)
The study aims to evaluate the efficacy of the completed concrete canal in the urban expansion area of the city of M’sila to prevent the flood risks of river Portem, by performing a hydraulic simulation using the 2D river simulation program HEC-RAS 2D and geographic information systems (SIG), in this research and after determining The water catchment, extraction of morphological characteristics, and calculation of the maximum flow quantity Qmaxm 3/s based on the series of rainfall data for the reed station for a period of 37 years after processing it spatially in geographic information systems. The areas exposed to the risk of flooding have a direct relationship with the period of return, so that an area of 9.98 hectares was recorded in the return period of 10 years, 12.72 hectares in 50 years, and 14.31 hectares in 100 years. The study also showed the importance of using HEC- RAS 2D and (SIG) in evaluating the efficiency of the concrete channel to prevent floods and contribute to decision-making to reduce the resulting disasters.